Inequities in Workplace Secondhand Smoke Exposure Among Nonsmoking Women of Reproductive Age - Johnson, Candice Y. (Am J Public Health, 2015)
Objectives. We characterized workplace secondhand smoke exposure among nonsmoking women of reproductive age as a proxy for workplace secondhand smoke exposure during pregnancy. Methods. We included nonsmoking women aged 18 to 44 years employed during the past 12 months who participated in the 2010 National Health Interview Survey. We estimated the prevalence of workplace secondhand smoke exposure and its associations with sociodemographic and workplace characteristics. Results. Nine percent of women reported workplace secondhand smoke exposure. Prevalence decreased with increasing age, education, and earnings. Workplace secondhand smoke exposure was associated with chemical exposure (prevalence odds ratio [POR] = 3.3; 95% confidence interval [CI] = 2.3, 4.7); being threatened, bullied, or harassed (POR = 3.2; 95% CI = 2.1, 5.1); vapors, gas, dust, or fume exposure (POR = 3.1; 95% CI = 2.3, 4.4); and worrying about unemployment (POR = 3.0; 95% CI = 1.8, 5.2), among other things. Conclusions. Comprehensive smoke-free laws covering all workers could eliminate inequities in workplace secondhand smoke exposure, including during pregnancy.